Research advances in immune agonists and their nanoparticles for enhancing the immunotherapeutic efficacy of PD-1 inhibitors in malignancies - Xia, Renjie; Liang, Juan; Ma, Jianguo; Du, Xiaoyu; Ma, Liangbin; Han, Xiongxiong; Wang, Yong; Qin, Jianwei; Yan, Long (Frontiers in Oncology, 2025)
Immune checkpoint blockade (ICB), particularly targeting programmed cell death-1 (PD-1), has revolutionized cancer immunotherapy but remains limited by heterogeneous therapeutic responses and immune-related toxicities. This review systematically examines the integration of immune agonists—STING, TLR, CD40, and OX40 agonists—with PD-1 inhibitors to overcome resistance and amplify antitumor immunity. Nanoparticle delivery systems emerge as transformative platforms, addressing critical limitations of free agonists, including enzymatic degradation, off-target toxicity, and poor pharmacokinetics. By leveraging tunable physicochemical properties (e.g., size, surface charge, stimuli-responsive release), nanoparticles enhance tumor-specific accumulation, prolong agonist half-life, and synergize with PD-1 inhibitors to remodel immunosuppressive microenvironments. Preclinical and early clinical studies demonstrate combinatorial strategies achieving increases in T cell infiltration and enhancements in anti-angiogenic activity compared to monotherapies. However, translational challenges persist, including nanoparticle-induced immunotoxicity (ROS-mediated inflammation), manufacturing scalability hurdles, and interspecies discrepancies in murine models. Future directions emphasize personalized nanovaccines, supramolecular cytosolic delivery systems (e.g., Calix-STING), and biomarker-driven trials to optimize efficacy in advanced pancreatic, melanoma, and immunologically quiescent tumors. This work underscores the imperative for interdisciplinary collaboration to standardize nanoparticle design and clinical validation frameworks, ultimately bridging the gap between nanomedicine innovation and oncology practice.